2014
DOI: 10.1177/1932296814532490
|View full text |Cite
|
Sign up to set email alerts
|

Use of the DISST Model to Estimate the HOMA and Matsuda Indexes Using Only a Basal Insulin Assay

Abstract: Type 2 diabetes mellitus (T2DM) has been declared an epidemic by the World Health Organization. 1 Treatment of T2DM individuals places considerable economic strain on health care systems worldwide. 2-4 However, it is hypothesized that early detection of T2DM can prompt intervention to delay the onset of symptoms, 5,6 and thus potentially reduce costs and improve quality of life. Insulin sensitivity (SI) is widely regarded as one of the better measures of the progression of an individual from normal glucose tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The model has several fixed parameters and limited samples, both of which may limit the robustness of identified values. However, the model has been proven to accurately describe dynamics to the limit the model defines them in both clinical use for glycemic control 25,41,47,48 and has demonstrated excellent accuracy in identifying insulin sensitivity and other metabolic characteristics. Regarding sampling rates, extra assays with a dense sampling grid are shown to not always improve identification, 5 where this work by Docherty et al showed subjecting a subject to extra samples may be unnecessary as sparser sampling is sufficient for robust identification.…”
Section: Limitationsmentioning
confidence: 99%
“…The model has several fixed parameters and limited samples, both of which may limit the robustness of identified values. However, the model has been proven to accurately describe dynamics to the limit the model defines them in both clinical use for glycemic control 25,41,47,48 and has demonstrated excellent accuracy in identifying insulin sensitivity and other metabolic characteristics. Regarding sampling rates, extra assays with a dense sampling grid are shown to not always improve identification, 5 where this work by Docherty et al showed subjecting a subject to extra samples may be unnecessary as sparser sampling is sufficient for robust identification.…”
Section: Limitationsmentioning
confidence: 99%